2013
DOI: 10.1080/11250003.2013.837105
|View full text |Cite
|
Sign up to set email alerts
|

Cephalopods in the diet of young-of-the-year bluefin tuna (Thunnus thynnusL. 1758, Pisces: Scombridae) from the southern Tyrrhenian Sea (central Mediterranean Sea)

Abstract: Information on distribution and abundance of cephalopods inhabiting pelagic water masses is often not available because of the difficulty of applying conventional methods in this remote habitat. An alternative source of information is represented by stomach content analysis of pelagic predators that are known to be efficient cephalopod prey collectors. This study focuses on the occurrence of cephalopod prey in the diet of young-of-the-year bluefin tuna (Thunnus thynnus L. 1758, Pisces: Scombridae) in the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…21,31,32 ). In the first life stages (FL in the range 17-48 cm), the low δ 15 N values (mean 5.1 ± 1.4‰) recorded in the YOY tuna specimens may be due to a diet starting on planktonic copepods and euphausiids, that could provide a high-energy food source for juvenile bluefin tuna during periods of rapid growth, and subsequently on small cephalopods 22,30,31,33,34 . Zooplankton may represent an overlooked prey base for YOY bluefin tuna in the Mediterranean Sea but information on the diet of such early juveniles is scanty (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…21,31,32 ). In the first life stages (FL in the range 17-48 cm), the low δ 15 N values (mean 5.1 ± 1.4‰) recorded in the YOY tuna specimens may be due to a diet starting on planktonic copepods and euphausiids, that could provide a high-energy food source for juvenile bluefin tuna during periods of rapid growth, and subsequently on small cephalopods 22,30,31,33,34 . Zooplankton may represent an overlooked prey base for YOY bluefin tuna in the Mediterranean Sea but information on the diet of such early juveniles is scanty (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Zooplankton may represent an overlooked prey base for YOY bluefin tuna in the Mediterranean Sea but information on the diet of such early juveniles is scanty (e.g. 22,30 ). Moreover, at the best of our knowledge, this is the first study evaluating the relationship between δ 15 N values and Fork Length (FL) in the Young Of Year (YOY) bluefin tuna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque la longitud furcal de los ejemplares estudiados fue de 131,73±16,32 cm, un valor significativamente superior a los individuos utilizados para este estudio, las presas mayoritarias fueron Engraulis encrasicolus y Sardina pilchardus, mientras que de entre los cefalópodos destacó la dominancia de Illex coindietii. Sin embargo, Battaglia et al, (2013), en su estudio sobre los cefalópodos como presa de juveniles de edad 0+ de atún rojo atlántico en el sur del Mar Tirreno obtuvo Onychoteuthis banksii y Heteroteuthis dispar como las especies con mayor índice de ocurrencia. Según los resultados obtenidos en el análisis de contenidos estomacales, las diferencias encontradas en la composición de la dieta del atún rojo atlántico de edad 0+ indican la existencia de una variabilidad tanto interanual como espacial en la dieta, la cual depende de la abundancia de presas potenciales en el hábitat explotado (Salman y Karakulak, 2009).…”
Section: Análisis De Contenidos Estomacalesunclassified
“…However, the extent of these excursions differs by species, and, according to current knowledge, the deepest dives are found in Xiphias gladius and Thunnus obesus , which probably have a more specialized visual system for dark environment (e.g., [ 26 ]). Recently, some authors observed high percentages of mesopelagic fish and cephalopod prey in the stomach content of Atlantic bluefin tuna (BFT), Thunnus thynnus , in different foraging areas of the Atlantic Ocean [ 27 ] and the Mediterranean Sea [ 23 , 25 , 28 , 29 ]; according to these studies, as well as tagging experiments [ 19 , 20 ], BFT is able to perform vertical excursions to match its food resources and feed on mesopelagic prey. The chance to encounter mesopelagic prey might increase during nighttime, when these species perform nycthemeral migrations (from deep waters toward upper layers).…”
Section: Introductionmentioning
confidence: 99%